Missionaries as bridge builders in Buddhist kingdoms: Amity amid radical difference - Pascal, Eva M. (Missiology, 2019)
Buddhism and Christianity are major world religions that both make universal and often competing claims about the nature of the world and ultimate reality. These claims are difficult to reconcile and often go to the core of Buddhist and Christian worldviews. This article looks at the age of encounter in the early modern period for ways Christians and Buddhists forged friendship through common spiritual commitments and action. Beyond seeking theological and philosophical exchange, convergences along spirituality and practice proved important vehicles for friendship. With the examples of Christian-Buddhist friendship from historical case studies, this article explores the ways contemporary Christian expressions of spiritual practice and advocacy allows Christians to connect with Buddhists. Early modern encounters have important lessons for furthering Christian-Buddhist friendship that may also be applied to other religious traditions.